2009
DOI: 10.3109/07357900902783195
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate Increases Expression of the Coxsackie and Adenovirus Receptor in Colon Cancer Cells

Abstract: Histone deacetylase inhibitors (HDACI), e.g., sodium butyrate (NaB), have been suggested to upregulate the coxsackie and adenovirus receptor (CAR). Its impact on CAR in colon carcinomas, however, is poorly understood. NaB treatment of colon cancer cells increased CAR expression preferentially in cell lines with low basic CAR levels. These findings suggest that downregulation of CAR gene expression is mediated by transcriptional regulation and that activation of the CAR gene promoter is modulated by histone ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…ASCL1 and CgA) and induces cell cycle arrest significantly, alters tumor cell proliferation and apoptosis in pheochromocytoma, which were indicated by the levels of cyclin D1, p21, cleaved PARP and cleaved caspase-3 proteins (30). NaBu also increases expression of the coxsackie and adenovirus receptor in colon cancer cells (31). Although some researchers have reported that NaBu induces human colon carcinoma HT-29 cell apoptosis through a mitochondrial pathway (32), we found a new relational molecular, ASC, whose expression was recovered in LS174T cells.…”
Section: Discussionmentioning
confidence: 53%
“…ASCL1 and CgA) and induces cell cycle arrest significantly, alters tumor cell proliferation and apoptosis in pheochromocytoma, which were indicated by the levels of cyclin D1, p21, cleaved PARP and cleaved caspase-3 proteins (30). NaBu also increases expression of the coxsackie and adenovirus receptor in colon cancer cells (31). Although some researchers have reported that NaBu induces human colon carcinoma HT-29 cell apoptosis through a mitochondrial pathway (32), we found a new relational molecular, ASC, whose expression was recovered in LS174T cells.…”
Section: Discussionmentioning
confidence: 53%
“…To date, mainly CAR downregulation in cancer types has been investigated. Hereby, activation of the Raf/MEK/ERK pathway and TGF- β signalling, hypoxia, epithelial–mesenchymal transdifferentiation and histone deacetylation of the CAR gene promoter were identified as regulators of CAR expression (Brüning and Runnebaum, 2003; Pong et al , 2003; Anders et al , 2003a; Lacher et al , 2006; Küster et al , 2010a, 2010b; Lacher et al , 2011). In contrast, few studies have investigated the mechanism of CAR upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these observations, significant correlations between impaired CAR expression and a poor clinical outcome for gastric and bladder cancer patients were found (Matsumoto et al , 2005; Anders et al , 2009). Regulation of declined CAR expression in cancers has been attributed to activation of the Raf/MEK/ERK pathway and the TGF- β signalling, as well as hypoxia, epithelial–mesenchymal transdifferentiation and histone deacetylation of the CAR gene promoter (Brüning and Runnebaum, 2003; Pong et al , 2003; Anders et al , 2003a; Lacher et al , 2006; Küster et al , 2010a, 2010b; Lacher et al , 2011). …”
mentioning
confidence: 99%
“…Histone deacetylation inhibitors are anti-neoplastic agents acting by net acetylation of core histones, causing the uncoiling of chromatin and activation of numerous genes implicated in the regulation of cell survival, growth, differentiation, cell cycle arrest and apoptosis (7,8,12,13). The activity of G 1 Cdks is stringently regulated by NaB through association with specific Cdk inhibitors including the CIP/KIP family (p21 ), which could bind all G 1 cyclin-Cdk complexes (8,14).…”
Section: Discussionmentioning
confidence: 99%